Pengaruh Latihan Jump Shoot Dan Bank Shoot Terhadap Kemampuan Shooting Pemain Klub Mranggen Selection Basketball - Ferdila Oktaviasari (YLPK Mahardhika, 2020)
The background of the problem in this study is the basketball club activity, Mranggen Selection Basketball, although in this study it is not directed to see the difference in a skill, but in plain view it is clear that there is a difference in the level of mastering the basic technique of shooting basketball. There are those who are good, moderate, and there are those who have not mastered shooting techniques optimally. As seen when shooting, the child was not maximal. Because there were problems when the students were shooting for the jump shoot, the child's accuracy level had not yet reached its peak. The research method used is quantitative research using true experimental method in the form of pretest-posttest control group design with two kinds of treatments. The population in this study were children who participated in the basketball club in Mranggen Selection Basketball. The sample in this study is the total population sampled for research with a total of 20 respondents. The sampling technique in this study used purposive sampling. The results of the study showed that the shooting exercise jumped on the basketball club participants. After giving push up and squat jump treatment, there was an increase in the shooting result, which was 5.30 where previously it was only 3.10. Through jump shoot practice, players are able to regulate the power or strength of the ball push properly so that the accuracy in shooting is more targeted. The conclusion of this study is that there is a significant effect of training with a jump shoot on shooting skills, there is a significant effect of training with a bank shoot on shooting skills. Key words: Jump Shoot, Bank Shoot, Shooting Latar belakang masalah pada penelitian ini yaitu pada kegiatan klub bola basket, Mranggen Selection Basketball walaupun dalam penelitian ini tidak diarahkan untuk melihat perbedaan suatu keterampilan tetapi secara kasat mata jelas terlihat adanya perbedaan tingkat dalam menguasai teknik dasar shooting bola basket. Ada yang sudah bagus,sedang, dan ada yang belum menguasai teknik shooting secara optimal. Seperti terlihat ketika melakukan shooting, anak kurang maksimal, Karena ada masalah pada saat siswa shooting untuk jump shoot tingkat akurasinya anak masih belum mencapai puncaknya. Metode penelitian ini yang digunakan yaitu penelitian kuantitatif yang menggunakan metode true eksperimental dalam bentuk pretest-posttest control group design dengan dua macam perlakuan. Populasi dalam penelitian ini adalah anak mengikuti klub bola basket di Mranggen Selection Basketball. Sampel dalam penelitian ini adalah jumlah keseluruhan populasi dijadikan sampel untuk penelitian dengan jumlah 20 responden. Teknik sampling pada penelitian ini menggunakan purposive sampling. Hasil penelitian menunjukkan latihan Jump shoot hasil shooting pada peserta klub mranggen basketball. Setelah di beri perlakuan / Treatment push up dan squat jump terdapat peningkatan hasil shooting adalah 5,30 dimana sebelumnya hanya 3,10. Melalui latihan jump shoot pemain mampu mengatur tenaga atau kekuatan dorongan bola dengan baik sehingga akurasi dalam melakukan shooting lebih terarah. Simpulan penelitian ini adalah ada pengaruh signifikan latihan dengan jump shoot terhadap kemampuan shooting, ada pengaruh signifikan latihan dengan bank shoot terhadap kemampuan shooting. Kata kunci : Jump Shoot, Bank Shoot , Shooting